2003
DOI: 10.1007/s00425-003-1051-2
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal variation in transcript accumulation in wood-forming tissues of maritime pine (Pinus pinaster Ait.) with emphasis on a cell wall glycine-rich protein

Abstract: Wood formation is being increasingly studied at cellular and biochemical levels; however, gene expression and regulation during wood formation remain poorly understood. Up to six types of wood can be studied within the same tree (early wood, late wood, juvenile wood, mature wood, reaction wood and opposite wood). These six types are characterized by different chemical, physical and anatomical properties. Using the cDNA-amplified fragment length polymorphism (AFLP) technique, we screened several thousand cDNA f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
57
0
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(60 citation statements)
references
References 48 publications
2
57
0
1
Order By: Relevance
“…A GRP with GXGX repeats from Pinus taeda (Allona et al, 1998;Zhang et al, 2000), as well as its proposed orthologous in Pinus pinaster (Le Provost et al, 2003), were found to be differentially expressed in the xylem of different wood types. It has been proposed that both Pinus proteins, reported as GRPs, might be involved in the determination of wood properties (Le Provost et al, 2003).…”
Section: Eucalyptus Clusters Encoding Grps With Gxgx Repeatsmentioning
confidence: 99%
“…A GRP with GXGX repeats from Pinus taeda (Allona et al, 1998;Zhang et al, 2000), as well as its proposed orthologous in Pinus pinaster (Le Provost et al, 2003), were found to be differentially expressed in the xylem of different wood types. It has been proposed that both Pinus proteins, reported as GRPs, might be involved in the determination of wood properties (Le Provost et al, 2003).…”
Section: Eucalyptus Clusters Encoding Grps With Gxgx Repeatsmentioning
confidence: 99%
“…These proteins involved in redox processes in the plant, as well as the extractives, among them polyphenols, tannins and resins, which are characterized as harmful components in the pulp and paper industry, are induced as a defense response to attack by pathogens, but also to abiotic stress (Breusegem et al, 2001). The Hsp are abundant in the xylem of P. pinaster (Le Provost et al, 2003) and Eucalyptus (Gonçalves et al, 2011), and are believed to have a specific function in the formation of wood, also important for the development of the secondary wood.…”
Section: Proteomic Characterization Of Eucalyptus Clonesmentioning
confidence: 99%
“…This transcriptome is considerably larger than other ones related to wood formation in conifers and available in databases, such as those of Pinus pinaster Ait. (Le Provost et al 2003), Pinus taeda L. (Kirst et al 2003) or Pinus radiata D. Don (Li et al 2010).…”
Section: De Novo Transcriptome Assemblymentioning
confidence: 99%
“…For instance, genes involved in wood formation have been identified in Pinus pinaster Ait. (Le Provost et al 2003), Pinus taeda L. (Kirst et al 2003) and Pinus radiata D. Don (Li et al 2010). More recently, Raherison et al (2015) and Lamara et al (2016) described networks of co-expressed genes involved in wood formation in Picea glauca (Moench) Voss, and Mishima et al (2014) published a transcriptomic analysis of wood formation in a Taxodiaceae, Cryptomeria japonica (Thunb.…”
Section: Introductionmentioning
confidence: 99%